A Life of Worry Politics, Mental Health, and Vietnam's Age of Anxiety - Tran, Allen L. (University of California Press, 2023)
In less than half a century, people in Vietnam have gone from fearing war and famine to fretting over the best cell phone plan. This shift in the landscape of people's anxieties is the result of policies that made Vietnam the second-fastest-growing economy in the world and a triumph of late capitalist development. Yet as much as people marvel at the speed of progress, all this change- even for the better-can be difficult to handle. A Life of Worry unpacks an ethnographic puzzle. What accounts for the simultaneous increase in anxiety and economic prosperity among Ho Chi Minh City's middle class? At a time when people around the world are turning to the pharmaceutical and wellness industries to soothe their troubled minds, it is worth asking whether these industries might be part of the problem. "A fascinating study of an important global phenomenon." - LI ZHANG, author of Anxious China: Inner Revolution and Politics of Psychotherapy "A Life of Worry takes us from Ho Chi Minh City's lively cafes to its burgeoning psychotherapy centers to offer an original phenomenological approach to anxiety as it is felt and enacted, often as a form of care for others, in Vietnam today." - JOCELYN LIM CHUA, author of In Pursuit of the Good Life: Aspiration and Suicide in Globalizing South India